Healthcare quality and safety assessment based on annual scorekeeping - Liang, Guo-Mo; Xie, Wen-Chao; Gan, Mei; Gao, Jiao-Wei; Liang, Qing; Zeng, Zhi-Yu (Frontiers in Public Health, 2022)
Offering quality healthcare is essential for the successful development of a hospital. The quality of healthcare and safety was enhanced in our hospital with the establishment of an assessment system involving doctors and other medical and technical personnel, with annual scorekeeping at its core. The content and scoring of the system were set up according to the characteristics of the different hospital departments, with an emphasis on the quality management of the whole treatment process, from the initial visit to the discharge of the patient. The system focused on the medical service and performance of the staff and involved a combination of incentives and penalties and a comprehensive quantitative assessment. It aimed to achieve the dynamic monitoring of individual and departmental performance and promote the high-quality development of the hospital.